Enhanced external counterpulsation ameliorates endothelial dysfunction and elevates exercise tolerance in patients with coronary artery disease - Yang, Huongrui; Song, Lixue; Ning, Xiang; Ma, Yanyan; Xue, Aiying; Zhao, Hongbing; Du, Yimeng; Lu, Qinghua; Liu, Zhendong; Wang, Juan (Frontiers in Cardiovascular Medicine, 2022)
The long-term effect of EECP on endothelial dysfunction and exercise tolerance, and the relationship between the changes in the endothelial dysfunction and exercise tolerance in the patients with coronary heart disease are still unclear. Our reach includes a total of 240 patients with CAD were randomly divided into EECP group (n =120) and control group (n = 120). All patients received routine treatment of CAD as the basic therapy. Patients in the EECP group received 35 1-h daily sessions of EECP during 7 consecutive weeks while the control group received the same treatment course, but the cuff inflation pressure was 0-10 mmHg. Peak systolic velocity (PSV), end diastolic velocity (EDV), resistance index (RI), and inner diameter (ID) of the right carotid artery were examined using a Color Doppler ultrasound. Serum levels of human vascular endothelial cell growth factor (VEGF), human vascular endothelial cell growth factor receptor 2 (VEGFR2), and human angiotensin 2 (Ang2) were determined by enzyme-linked immunosorbent assay (ELISA). Exercise load time, maximal oxygen uptake (VO2max), metabolic equivalent (METs), anaerobic threshold (AT), peak oxygen pulse (VO2max/HR) were assessed using cardiopulmonary exercise tests. After one year follow-up, the EDV, PSV and ID were significantly increased in the EECP group. The serum levels of VEGF and VEGFR2 were elevated in the EECP and control groups. As for exercise tolerance of patients, there were significant increases in the exercise load time, VO2max, VO2max/HR, AT and METs in the EECP group and VO2max and METs in the control group. The changes in VEGF, EDV and PSV were positively and independently associated with the changes in METs after adjustment for confounders including age and the medication of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. The data of our study suggested that EECP is a useful therapeutic measurement for amelioration of endothelial dysfunction and long-term elevation of exercise tolerance for patients with coronary heart disease.